Introduction of Methods to Reduce and Remove Patulin from Food Products - Parisa ZIARATI; Faezeh SHIRKHAN; Mahdieh MOSTAFIDI; Maryam Tamaskani ZAHEDI; Barbara SAWICKA (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Food Science and Technology, 2019)
Patulin is a mycotoxin produced by different species of fungi of the genus Penicillium and Aspergillus, found in several species of fruit, and significant in apples. The purpose of this investigation is to the theoretical study of food contamination mechanisms by patulin and hazard of patulin for health. Various methods of determination of patulin and the possibility of reducing its level in apple-based products were analyzed. To reduce and remove patulin, several methods have been proposed that include post-harvest patulin control in products, pre-treatment control, and control by using physical and chemical methods, post-processing control such as packaging and using methods such as activated carbon or lactic acid bacteria. The standards and comparing the amount of patulin with them can be an important help in controlling this substance throughout the production processing of safe food.